Room temperature hydrogen sensing with the graphite/ZnO nanorod junctions decorated with Pt nanoparticles. (February 2016) - Yatskiv, R.; Grym, J.; Gladkov, P.; Cernohorsky, O.; Vanis, J.; Maixner, J.; Dickerson, J.H.
Highlights: A simple method for the fabrication of nanostructured ZnO sensors is reported. The sensing mechanism is described in terms of the Schottky barrier variation. Structural and optical properties of the EPD deposited ZnO films are discussed. Abstract: We report on the performance of solution-processed hydrogen sensors based on vertical arrays of ZnO nanorods with Schottky contacts. The vertical arrays of ZnO nanorods are grown by a low temperature hydrothermal method on a seed layer consisting of electrophoretically deposited ZnO nanoparticles. A Schottky contact on the ZnO nanorod arrays is created by the deposition of graphite from a colloidal solution. The structure of the graphite/ZnO nanorod system is shown to be sensitive to hydrogen at room temperature. The hydrogen sensing properties are further enhanced by the decoration of the graphite/ZnO nanorod interface with Pt nanoparticles. The sensing response is improved by a factor of 100, and faster recovery and response times are observed.